2021
DOI: 10.1007/s11845-021-02748-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic coding of chronic physical conditions in Irish general practice

Abstract: Background Chronic conditions are responsible for significant mortality and morbidity among the population in Ireland. It is estimated that almost one million people are affected by one of the four main categories of chronic disease (cardiovascular disease, chronic obstructive pulmonary disease, asthma, and diabetes). Primary healthcare is an essential cornerstone for individuals, families, and the community and, as such, should play a central role in all aspects of chronic disease management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…A national-level survey conducted back in 2011 also stressed increased staff workload and lack of appropriate funding as the critical barrier to CDM implementation in Irish general practices [ 11 ]. Similar issues has been highlighted in the international literature [ 18 , 19 ] and our group has previously reported on the importance of expanding practice nursing for Irish general practice [ 24 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A national-level survey conducted back in 2011 also stressed increased staff workload and lack of appropriate funding as the critical barrier to CDM implementation in Irish general practices [ 11 ]. Similar issues has been highlighted in the international literature [ 18 , 19 ] and our group has previously reported on the importance of expanding practice nursing for Irish general practice [ 24 ].…”
Section: Discussionsupporting
confidence: 79%
“…In the UK, Anwar et al noted that general practices in deprived areas had significantly higher burdens of chronic diseases, with access to care in busy practices becoming increasingly difficult [ 17 ]. Pericin et al identified the inadequacy of coding of chronic diseases in Irish general practices as a potential barrier to implementation of structured care [ 18 ].…”
Section: Introductionmentioning
confidence: 99%